Transcriptome profiling of abdominal aortic tissues reveals alterations in mRNAs of Takayasu arteritis - Yuqing, Miao; Shang, Gao; Qing, Gao; Jiyang, Wang; Ruihao, Li; Zuoguan, Chen; Yongpeng, Diao; Zhiyuan, Wu; Yongjun, Li (Frontiers in Genetics, 2022)
Takayasu arteritis (TA) is a chronic granulomatous vasculitis involving in the main branches of aorta. Previous studies mainly used peripheral blood and some vascular tissues but seldom studies have sequenced vascular tissues. Here in this study, we aimed to explore the alterations of mRNA in TA by performing bulk RNA sequencing. A total of 14 abdominal aortic tissues including 8 from renal transplantation and 6 from patient with TA undergoing bypass surgeries. Bulk-RNA sequencing were performed and after the quality control, a total of 1897 transcripts were observed to be significantly differently (p<0.05 and Log2FC>1) expressed between the TA and control group, among which 1361 transcripts were in TA group and 536 in the Control group. Reactome Pathway Enrichment Comparison analysis revealed interleukin-10 signaling and signaling by interleukins were highly expressed in TA group. Besides, extracellular matrix organization was also observed in this group. WGCNA and PPI obtained 20 core genes which were highly correlated with the clinical phenotype. We then also perform deconvolution of the bulk RNA-seq data by using the scRNA-seq dataset and noticed the high proportion of SMCs in our dataset. Furthermore, in line with our bioinformatic analysis, immunohistochemical staining revealed high expression of IL-1R1 and IL-1R2 in the aortic tissues of TA. Briefly, this study revealed critical roles of interleukins in TA pathogenesis, and SMCs may also participate in the reconstruction in vessel wall at late stage of TA.